PERSEPSI WISATAWAN DOMESTIK TERHADAP PEKERJA TATO TEMPORER DI DAYA TARIK WISATA PENELOKAN KECAMATAN KINTAMANI KABUPATEN BANGLI - Astina, I Gede Telaga; Pujani, Ni Luh Kerti (JURNAL DESTINASI PARIWISATA; Vol 3 No 1 (2015): VOL 3, NO 1 (2015): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i01.p10, 2015)
ABSTRACT The background of this research is the existence of a negative impression caused by the temporary tattoo services as their performances were less polite and the tattooed their bodies scare the visitors. In addition, for the most part of the tattoo service providers who offer their services to visitors to demand. The purpose s of this study are determine the perception of tourists to workers and temporary tattoos to determine why local communities choose to work as temporary tattoos. T he data are collected through observation, questionnaires and structured interviews. Taking samples by the method of proportional purposive sampling as many as 50 people. Techniques for tourist using quota sampling methods, data analysis technique used is descriptive qualitative research to illustrate how objects and using a Likert scale analysis to analyze the perceptions of tourists to workers temporary tattoos. The results of this research is the perception of domestic travelers to workers, temporary tattoos undecided, it shows that on the one hand workers are still expected existence of temporary tattoos and more travelers on the other hand if the workers want no temporary tattoos Because of their attitudes and behaviors that are Considered impolite cause uncomfortable. For tourists feel less reason to Encourage residents to work as a temporary tattoo that is due to spend leisure time, limited employment opportunities, parent recommendation.
Keywords: Perception, motivation, Temporary Tattoos